Pediatric Aerodigestive Foreign Bodies - Margaret Wolff; Stuart Bradin; Rakesh Mistry (Association of American Medical Colleges, 2014)
Abstract Introduction The purpose of this case-based module is to teach health care professionals about the presentation, evaluation, and management of aerodigestive foreign bodies in children. Aerodigestive foreign bodies are common in children and can result in significant morbidity if not recognized and managed appropriately. This requires a familiarity with this topic because the evaluation and management varies based on the patient's symptoms, object ingested or aspirated, and location of the foreign body. We saw a need to develop this module for our residents and fellows that work in our pediatric emergency department to standardize the approach to these patients. Methods The module consists of a pre- and posttest, a PowerPoint presentation with embedded review questions, and a small-group exercise (think-pair-share). This module is designed to be used in a group classroom and requires approximately 55 minutes. Prior to the session, the instructor should review the lecture notes that accompany the PowerPoint presentation to become familiar with the concepts and the slides. Results The mean score on the pretest was 53% compared to a mean score of 85% correct on the posttest. In addition, 93% of learners successfully created an algorithm for the management and evaluation of a patient with a suspected aspirated foreign body and 96% of learners were able to complete the suspected gastrointestinal foreign body algorithm. Discussion This module references recent research providing evidence based guidance to the approach and management of aerodigestive foreign bodies. We believe this is an effective module that will be useful for anyone involved in the care of children.